Mixed legume–grass seeding and nitrogen fertilizer input enhance forage yield and nutritional quality by improving the soil enzyme activities in Sichuan, China - Tahir, Muhammad; Wei, Xiao; Liu, Haiping; Li, Jiayi; Zhou, Jiqiong; Kang, Bo; Jiang, Dongmei; Yan, Yanhong (Frontiers in Plant Science, 2023)
Information regarding relationships between forage yield and soil enzymes of legume–grass mixtures under nitrogen (N) fertilization can guide the decision-making during sustainable forage production. The objective was to evaluate the responses of forage yield, nutritional quality, soil nutrients, and soil enzyme activities of different cropping systems under various N inputs. Alfalfa (Medicago sativa L.), white clover (Trifolium repens L.), orchardgrass (Dactylis glomerata L.), and tall fescue (Festuca arundinacea Schreb.) were grown in monocultures and mixtures (A1: alfalfa, orchardgrass, and tall fescue; A2: alfalfa, white clover, orchardgrass, and tall fescue) under three N inputs (N1: 150 kg ha−1; N2, 300 kg ha−1; and N3: 450 kg ha−1) in a split plot arrangement. The results highlight that A1 mixture under N2 input had a greater forage yield of 13.88 t ha−1 year−1 than the other N inputs, whereas A2 mixture under N3 input had a greater forage of 14.39 t ha−1 year−1 than N1 input, but it was not substantially greater than N2 input (13.80 t ha−1 year−1). The crude protein (CP) content of grass monocultures and mixtures significantly (P < 0.05) increased with an increase in the rate of N input, and A1 and A2 mixtures under N3 input had a greater CP content of 18.91% and 18.94% dry matter, respectively, than those of grass monocultures under various N inputs. The A1 mixture under N2 and N3 inputs had a substantially greater (P < 0.05) ammonium N content of 16.01 and 16.75 mg kg−1, respectively, whereas A2 mixture under N3 had a greater nitrate N content of 4.20 mg kg−1 than the other cropping systems under various N inputs. The A1 and A2 mixtures under N2 input had a substantial higher (P < 0.05) urease enzyme activity of 0.39 and 0.39 mg g−1 24 h−1 and hydroxylamine oxidoreductase enzyme activity of 0.45 and 0.46 mg g−1 5 h−1, respectively, than the other cropping systems under various N inputs. Taken together, growing legume–grass mixtures under N2 input is cost-effective, sustainable, and eco-friendly, which provide greater forage yield and improved nutritional quality by the better utilization of resources.